The influence of Symmetrical Pulsating AC power input to the efficiency of a single phase transformer - Sharida Johari (School of Electrical Systems Engineering, 2009)
This final year project is to describe about the influence of symmetrical pulsating AC power input to the efficiency of a single phase transformer. In this work, the efficiency of transformer is determined by measuring the output and input power. The secondary side of transformer is connected to a single phase AC induction motor. For comparative needs, the measurement is done with pure AC voltage (output of Schaffner equipment) and indirect method where the AC voltage controller is inserted between Schaffner and load where the measurement is equipped with two harmonic analyzer (PM100). The results show that the efficiency of transformer decrease with symmetrical pulsating AC power input.